MEASURING EARNINGS MANAGEMENT PRACTICES USING THE M-SCORE BENEISH MODEL FOR IRAQI BANKS LISTED ON THE IRAQ STOCK EXCHANGE (World Economics and Finance Bulletin, 2023)
One of the most widespread practices that affect the quality of the company's financial reports is earnings management, as earnings management affects the process of showing the real performance of companies by exploiting flexibility in GAAP accounting principles). The use of the M-score model is important in discovering earnings management practices and has been applied the search on the 16 Iraqi banks listed in the Iraq Stock Exchange for the year 2018. The research found that the number of banks that manage their profits in the year 2018 according to the M-score model is nine banks, which constitutes 56.2% of the total sample of 16 banks listed in the market. Iraq Securities, the remaining 43.75% do not practice earnings management, while the research recommended the employment of statistical models (especially the M-score model) by external auditors to detect earnings management practices, as it is a useful technique and a good means that can be added to other control measures that they use in auditing the accounts of companies